HUBUNGAN MOTIVASI SISWA PUTRA DAN PUTRI DALAM MENGIKUTI MATA PELAJARAN PENDIDIKAN JASMANI - Prayoga, Riris Novrian; Nurseto, Frans; Adam, Usman (JUPE, 2015)
This study aimed to obtain empirical data on how motivated boys and girls students in following the subjects of physical education. Quantitative research with the type of research method used was a survey by using correlational analysis of statistical data. The collection of data is in the form of motivation using questionnaires and physical education lessons using daily values. The sample used 75 students from a population of 530 students. Based on the results of correlation analysis: it showed that the motivation factor has a relationship with a male student studying physical education at 0.472. Correlation of female student motivation to study physical education is 0.408, it means there is a relationship. While the motivation correlation of male and female students in physical education subjects are 0.552. The conclusion of this study showed that there is a significant relationship between motivation of male and female students in following physical education of subjects.Penelitian ini bertujuan untuk mendapatkan data secara empiris tentang seberapa besar motivasi siswa putra dan putri dalam mengikuti mata pelajaran pendidikan jasmani. Penelitian kuantitatif dengan jenis metode penelitian yang digunakan adalah survei dengan analisis data statistik menggunakan korelasional. Pengumpulan data yang berupa motivasi menggunakan angket dan pelajaran pendidikan jasmani dengan menggunakan nilai harian. Sampel yang digunakan 75 siswa dari populasi yang berjumlah 530 siswa. Berdasarkan hasil analisis korelasional, menunjukkan bahwa faktor motivasi siswa putra memiliki hubungan dengan belajar pendidikan jasmani sebesar 0,472. Korelasi motivasi siswa putri dengan belajar pendidikan jasmani sebesar 0,408, artinya memiliki hubungan. Sedangkan korelasi motivasi siswa putra dan putri dalam mengikuti mata pelajaran pendidikan jasmani sebesar 0,552. Kesimpulan penelitian ini menunjukan ada hubungan signifikan antara motivasi siswa putra dan putri dalam mengikuti mata pelajaran pendidikan jasmani.Kata kunci : korelasi, motivasi, pendidikan jasmani.Â